2020
DOI: 10.3390/cancers12061498
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids in Cancer Metastasis

Abstract: Metastasis represents a serious complication in the treatment of cancer. Flavonoids are plant secondary metabolites exerting various health beneficiary effects. The effects of flavonoids against cancer are associated not only with early stages of the cancer process, but also with cancer progression and spread into distant sites. Flavonoids showed potent anti-cancer effects against various cancer models in vitro and in vivo, mediated via regulation of key signaling pathways involved in the migration and invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
135
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(138 citation statements)
references
References 129 publications
(194 reference statements)
2
135
0
1
Order By: Relevance
“…Currently, extensive research is being performed for possible applications of natural products for the therapy of chronic diseases, as these agents can regulate multiple molecular targets and transcription factors [ 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 ]. In the present review, a comprehensive discussion of possible impact of Res on the TGF-β signaling pathway, which is one of the important cascades involved in the regulation of biological mechanisms and the generation of pathological events, is provided.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, extensive research is being performed for possible applications of natural products for the therapy of chronic diseases, as these agents can regulate multiple molecular targets and transcription factors [ 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 ]. In the present review, a comprehensive discussion of possible impact of Res on the TGF-β signaling pathway, which is one of the important cascades involved in the regulation of biological mechanisms and the generation of pathological events, is provided.…”
Section: Discussionmentioning
confidence: 99%
“…More than 8000 phenolic compounds from plants have been reported, and the half of phenolic compounds is flavonoids presenting as aglycone, glycosides, and methylated derivatives [167]. Flavonoids have several subgroups which include flavonols, flavones, flavanonols, flavanols, flavanones, anthocyanidins, chalcones, and isoflavones [5,168]. Non-flavonoids compounds include phenolic acids, tannins, coumarins, lignans, and stilbens [169].…”
Section: Classification and Dietary Sources Of Phytochemicalsmentioning
confidence: 99%
“…Metastasis represents a serious complication in cancer treatment. Studies have shown flavonoids have anti-cancer effects by regulating key signaling pathways involved in critical steps of metastatic spread in several in vitro and in vivo models [ 5 , 182 ]. Epigenetic changes could occur in the early stages of carcinogenesis preceding genetic mutations, so epigenetics are considered to be promising targets for early interventions against cancer using epigenetic biologically active substances [ 3 ].…”
Section: Overview Of Phytochemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these compounds can support cancer prevention and therapy or overcome cancer drug resistance with few or no side effects. Flavonoids, for example, suppress cancer through modulation of extracellular matrix (ECM) proteins, inhibition of the epithelial–mesenchymal transition (EMT), and inhibition of cancer cell metabolism [ 13 , 14 ]. Plant phenolic acids and lichens upregulate apoptosis, inhibit proliferation and metastasis, and induce cell cycle arrest, while vanilloids such as capsaicin exert anticancer effects through the modulation of intracellular calcium signaling [ 15 , 16 , 17 ].…”
Section: Natural Substances In the Prevention And Treatment Of Neumentioning
confidence: 99%